Twee onversoenbare konstrukte "n resente historiese Jesus-navorsing: R W Funk en W Schmithals 1 - Wyk, D. J. C. van (Hervormde teologiese studies, 2000)
Two Incompatible constructs in recent historical Jesus research: R W Funk and W Schmithals. The article discusses the similarities and differences between the work of Robert Funk and Walter Schmithals w'th regard to the discontinuity between the pre-Easter Jesus of history and the post-Easter Jesus of faith. The article focuses on the 1994 publication of Schmithals, Theologiegeschichte des Urchristentums, and the 1996 pubilcation of Funk, Honest to Jesus. According to Schmithals, Jesus was embedded in apocalypticism, while h's post-Easter followers projected wisdom teaching into his message. According to Funk, the pre-Easter Jesus was a sub-versive wisdom teacher, while his post-Easter followers interpreted his vision on the Kingdom of God from an apocalyptic perspective. Funk's emphasis criticizesthe kerygma as an alienation from Jesus. Schmithals, emphas's is a critical endorsement of the kerygma.